CARBONO E ATIVIDADE DA BIOMASSA MICROBIANA DO SOLO EM DIFERENTES SISTEMAS DE PRODUÇÃO NO CERRADO, MS - SCHNECKEMBERG, Luiz Fernando López; PERES, Nathália Dias; MATEUS, Yasmin Hikari Ueno; SCHIAVO, Jolimar Antonio (ANAIS DO ENIC, 2026)
.